A Novel Watermarking Approach Based On Singular Value Decomposition - Gudware, Deepali (International Journal of Computer Sciences and Engineering, 2025)
Digital media, like video, audio, images and multimedia documents can be protected against copyright infringements with imperceptible, incorporated patterns. Such methods are based on steganography and digital watermarking techniques. Digital watermarking technology can provide persistent identification of copyrighted subject matter to facilitate rights management in the emerging complex hybrid digital/analog devices and home networks. For both analog and digital content, digital watermarks enable copyright holders to protect their content from unauthorized use, as well as enable content owners to effectively communicate their copyrights, monitor use of their content, and track unauthorized distribution of licensed content. Most watermarks are inserted as a plain-bit or adjusted digital signal using a key-based embedding algorithm. The embedded information is hidden and linked inseparably with the source data structure. For the most favourable watermarking application, a trade-off between opposing criteria like robustness, non-perceptibility, non-detectability and protection include to be ended. Most watermarking algorithms are not resistant in opposition to all attacks, and even gracious attacks like file and data modifications can demolish the watermark very easily.